2014
DOI: 10.1080/00032719.2014.888725
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Lead Distribution in Marine Soil Sediments, Terrestrial Soil, Terrestrial Rock, and Atmospheric Particulate Matter around Split, Croatia

Abstract: The distributions of cadmium and lead in marine sediments, surrounding soil, stones, and atmospheric particulate matter were determined at different locations in Split, Croatia. The determination of cadmium and lead was performed by flame atomic absorption spectrometry whereas atmospheric particulate matter samples were analyzed by inductively coupled plasma-optical emission spectrometry. Cadmium concentrations in the stones and soil were between 0.2 to 0.6 lg g À1 and 0.2 to 0.9 lg g À1 . The concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Lead is one of the primary contaminants present in the environment 8,19 and naturally occurs in rocks, soils and in the hydrosphere. 48 However, Pb is also the most widely used metal and industrial Pb contributes a considerable quantity to that found in the natural environment. 49 Large amounts of lead tetraethyl can be completely converted to aerosols through the combustion of gasoline, subsequently contributing to atmospheric Pb.…”
Section: Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead is one of the primary contaminants present in the environment 8,19 and naturally occurs in rocks, soils and in the hydrosphere. 48 However, Pb is also the most widely used metal and industrial Pb contributes a considerable quantity to that found in the natural environment. 49 Large amounts of lead tetraethyl can be completely converted to aerosols through the combustion of gasoline, subsequently contributing to atmospheric Pb.…”
Section: Leadmentioning
confidence: 99%
“…Lead is one of the primary contaminants present in the environment and naturally occurs in rocks, soils and in the hydrosphere . However, Pb is also the most widely used metal and industrial Pb contributes a considerable quantity to that found in the natural environment .…”
Section: Toxic Metalsmentioning
confidence: 99%
“…The organic compounds of lead are more toxic than mineral compounds and are more easily absorbed by the gastrointestinal tract. Most toxic lead groups are methyl or ethyl [32,33]. In accordance with regulations of South African Ministry of Health, the maximum lead level in fresh and processed fish is 0.5 mg/kg and the maximum lead limit by the European Commission has been approved 0.3 mg/kg [34,35].…”
Section: Leadmentioning
confidence: 99%
“…For example, organic materials are introduced into soils through the excessive use of fertilizers and pesticides by farmers [ 2 , 3 ]. In contrast, heavy metal contamination in soils is typi­cally caused by industrial activities, such as mining and mineral processing [ 4 , 5 ]. Therefore, soils origi­nating from different locations, regions or countries tend to be unique in composition.…”
Section: Introductionmentioning
confidence: 99%